A Comparative Study on Objective Functions of Product Rate Variation and Discrete Apportionment Problems - Thapa, Gyan Bahadur (Journal of Institute of Science and Technology, 2015)
Setting the proper objective functions to optimize the decision making situations is prevalent in most of the mathematical programming problems. In this paper, we formulate the mathematical models of product rate variation and discrete apportionment problems. Furthermore, a brief comparative study of the objective functions to both the problems is reported in terms of inequality measures, precisely indicating the equitably efficient frontier for production rate variation problem via discrete apportionment. The largest reminder algorithm and rank-index algorithm for the apportionment problem are discussed briefly. Journal of Institute of Science and Technology, 2014, 19(1): 69-74